Structural Changes by Thermal Treatment up to Glass Obtention of P2O5-Na2O-CaO-SiO2 Compounds with Bioglass Composition Types - Volzone, Cristina (2013)
P2O5-Na2O-CaO-SiO2 compounds are the base of certain glass types. Glasses are solids obtained by fast cooling of melted mix of certain compounds. Different compositions give origin to many products with a variety of applications such as: bottles, coatings, windows, tools for chemical industry, laboratory equipment, optics, as bioceramics, etc. The aim of this work was to analyze structural changes of different composition in the P2O5-Na2O-CaO-SiO2 systems thermally treated up to 1250˚C, that is to say, before glass formation, by X ray diffraction. Intermediate and final developed phases up to 1100˚C thermal treatment in samples were generated as a function of Na2O/CaO (1 and 1.62) and P2O5/Na2O ratios (0, 0.2 and 0.245). High- and low-combeites, calcium and sodium-calcium silicate were found at the highest studied temperature.